The effect of G-CSF and AMD3100 on mice treated with streptozotocin: Expansion of alpha-cells and partial islet protection. (August 2017) - Gomez, Yonathan; Diaz-Solano, Dylana; Gledhill, Teresa; Wittig, Olga; Cardier, Jose
Highlights: Hematopoietic progenitor stem cells (HPSCs) are mobilized to damaged tissues. Streptozotocin (STZ) induces damage of beta-cells in pancreatic islets. G-CSF and AMD3100 partially protect pancreatic islets in mice treated with STZ. G-CSF and AMD3100 induces expansion of alpha-cells. G-CSF and AMD3100 did not protect beta-cells damage induced by STZ. Abstract: Administration of streptozotocin (STZ) is one of the most used experimental models of diabetes (STZ-DT). STZ induces beta-cell damage in pancreatic islets. It is known that hematopoietic stem progenitor cells (HSPCs) are mobilized from bone marrow to damaged tissues. In this work, we evaluated the effects of the hematopoietic mobilizers G-CSF (250 μg/kg; for five consecutive days) and AMD3100 (5 mg/kg; single s.c injection) in mice treated with STZ (175 mg/kg). Mice injected with STZ showed a significant reduction in the number and area of islets and in the number of beta- and alpha-cells. Concurrently, they had hyperglycemia (blood glucose over 300 mg/dl) associated with very low levels of insulin in plasma. The number and area of islets from STZ-DT mice treated with G-CSF and/or AMD3100 were similar to the controls. However, these mice had neither a reduction of hyperglycemia nor an improvement in the insulin levels. Analysis of islet cellularity showed a large reduction in beta-cells with a significant expansion of alpha-cells. These results indicate that G-CSF and AMD3100 induce partial protection of islet tissues and expansion of alpha-cells in mice treated with STZ but do not protect beta-cells from the damage induced by this compound.